2013
DOI: 10.1063/1.4773103
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the energy flux at the substrate position during magnetron sputter deposition processes

Abstract: Articles you may be interested in Investigation of ionized metal flux in enhanced high power impulse magnetron sputtering discharges Steady state discharge optimization in high-power impulse magnetron sputtering through the control of the magnetic field Hysteresis behavior during reactive magnetron sputtering of Al 2 O 3 using a rotating cylindrical magnetron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Magnetron Sputtering (HiPIMS) discharges were ignited successively. More details about the experimental setup and the HiPIMS pulse can be found in [9] and [10]. To study the influence of each discharge type, pressure and averaged power were set to 0.66 Pa (Argon) and 400 W,…”
Section: Magnetron (Dcms) Pulsed DC Magnetron (Pdcms) and High Pomentioning
confidence: 99%
“…Magnetron Sputtering (HiPIMS) discharges were ignited successively. More details about the experimental setup and the HiPIMS pulse can be found in [9] and [10]. To study the influence of each discharge type, pressure and averaged power were set to 0.66 Pa (Argon) and 400 W,…”
Section: Magnetron (Dcms) Pulsed DC Magnetron (Pdcms) and High Pomentioning
confidence: 99%
“…A well characterized probe using a commercially available heat flux probe [14,28,65,66] based on thermopile (a stack of thermo couples) sensors has been used by Thomann, Dussard and coworkers for measurements in different plasma environments.…”
Section: Thermopile Sensormentioning
confidence: 99%
“…The different probe types and designs have been used for characterization of various plasmas which are used in materials processing, such as different types of magnetron discharges (dc [23,1,[17][18][19][20][21][22], rf [20,22,24], HiPIMS [25][26][27][28]) and hollow cathode arcs [29][30][31] for thin film deposition purposes. Also rf [24,[32][33][34][35][36] or microwave [24] plasmas and ion beams [37] for surface modification have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages related to HIP-IMS is the "cooler plasma" that reaches the substrate. By measuring the ion flux at the substrate position during HIPIMS and DC [23], it was shown that the energy per deposited atoms during a HIPIMS process is smaller than during DCMS or Pulsed DCMS. This is a direct result of the increased gas phase collision frequency of the sputtered and the sputtering species which, in the substrate vicinity (some 10 cm from the metal source), has also been shown to result in ion and electron temperatures close to room temperature in the substrate vicinity.…”
Section: Deposition On Temperature Sensitive Substratesmentioning
confidence: 99%